HUMAN RIGHTS IMPLEMENTATION HEALTH SERVICE - Anggraeni Endah Kusumaningrum (Surakarta Law and Society Journal, 2018)
Health rights are human rights inherent in a person because of his birth as a human being, and not because of the giving of someone or the state therefore it cannot be revoked and violated by anyone. Health rights must be able to become one of the main benchmarks of development and prosperity of a nation. Therefore health must be mid-stream development, which is continuous sustainable development. The implementation of human rights is carried out by creating equality of access to health services, preventing actions that can reduce the health status of the community, preventing actions that can reduce the health status of the community, and making health policies and providing health services and budgets appropriate and adequate for the entire community. Keywords: Human Rights, Health Services.